The ATLAS inner detector trigger performance in pp collisions at 13 TeV during LHC Run 2. - Beauchemin, P. H.; Croft, V..; Drobac, A. S.; Kaya, F. I.; Sliwa, K..; Son, H.. (Tufts University. Tisch Library., 2022)
Springer Open.